Tingkat Adopsi Software Akuntansi Cloud-Based pada UMKM dengan Faktor Pendorong dan Penghambat - Sri Ambar Wati; Agus Munandar (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to identify the adoption rate of cloud-based accounting software among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, through an evaluation of several factors that drive and hinder its adoption. The method used in this study is a Systematic Literature Review (SLR), which involves obtaining and analyzing published scientific journals from 2021 to 2025 using keywords such as "adoption of MSME technology," "cloud accounting software," "driving and inhibiting factors," and "MSME digitalization." The results of this analysis indicate that the adoption rate of cloud-based accounting software by MSMEs generally remains at the early majority to laggard stage, with key driving factors including ease of use, operational efficiency, and increased financial data accuracy. Conversely, the dominant inhibiting factors are low levels of technological literacy, limited human resources, and a lack of supporting infrastructure. This study also found that increased software adoption can have a positive impact on business performance, particularly in sales and financial recording. To overcome these obstacles, ongoing training and mentoring are recommended, as well as increasing the availability of digital facilities and infrastructure. These findings provide strategic implications for policies and MSMEs in optimizing the use of cloud-based accounting technology in their operations to support national economic growth.